1996
DOI: 10.1084/jem.183.3.821
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin functions as an inflammatory mediator through activation of its receptor.

Abstract: SummaryA rat model of inflammation was used to investigate the biological effects of thrombin. The thrombin-specific inhibitor Hirulog TM markedly attenuated the carrageenin-induced edema of the paw of the rat. Injection of thrombin into the paw also produced edema. The effect of thrombin was due to activation of its receptor; a thrombin receptor activating peptide (TRAP) reproduced the effects of thrombin in causing edema. TRAP also increased vascular permeability as demonstrated by extravasation of Evans blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
174
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(182 citation statements)
references
References 30 publications
5
174
2
1
Order By: Relevance
“…7B). Incubating HSCs with 50 mol/L of PAR 1 antagonist abrogated p46 Shc and p52 Shc phosphorylation induced by thrombin and SF-NH 2 (Fig. 7B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…7B). Incubating HSCs with 50 mol/L of PAR 1 antagonist abrogated p46 Shc and p52 Shc phosphorylation induced by thrombin and SF-NH 2 (Fig. 7B).…”
Section: Resultsmentioning
confidence: 99%
“…7C). Exposure to anti-PAR 1 abolished the Shc/Grb2 complex formation triggered by thrombin and SF-NH 2 (Fig. 7C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have also shown a pro-inflammatory role for PAR 1 activation (Cirino et al 1996,Vergnolle et al 1999b, and most recently, we have demonstrated that PAR 4 agonists induced oedema and granulocyte infiltration when injected into the rat paw (Hollenberg et al 2004). …”
Section: Pars and Inflammationmentioning
confidence: 99%